Gathering the views of children and young people to inform practice in a psychological service. Issue 4 (November 2014) - Alexander, Shona; Brown, Neil; Farmer, Kait; Fraser‐Smith, Jenny; McClatchey, Kirstie; McKeown, Vibeke; Sangster, Ali; Shaver, Isabel; Templeton, Jenny
<x xml:space="preserve">Abstract</x> This paper describes the process employed by a psychological service to gather the views of children and young people using guided discussion groups and questionnaires. Pupils in the guided discussion groups were asked to identify issues that affect them and how adults could help. This information was analysed using thematic analysis. Seven themes were identified as issues: managing feelings; friendships; behaviour; specific difficulties that can affect learning; not being accepted; bullying; and 'other important issues', including bereavement and family difficulties. In relation to each of these themed issues, several sub‐themes regarding how adults could help were collated. Questionnaire data was analysed using inferential statistics. The questionnaire rated the importance of help from adults in the areas of learning, friendships and feelings. Results suggested that these were equally important to primary‐aged pupils. Findings were used to contribute to the development plan and shape future practice.